Construction Waste Management Modern Strategies for Recycling and Promoting Sustainability in Building Projects - حنان بلقاسم عيسى (African Journal of Advanced Pure and Applied Sciences, 2025)
The study analyzes construction waste management and explores recycling strategies to promote sustainability in light of global technological and environmental changes. It highlights the potential for transforming construction and demolition waste from a burden into a valuable economic resource through recycling, supported by collaboration with skilled private sector companies. This transformation could reduce reliance on imported raw materials such as iron and steel. The study examines waste management mechanisms, types, and the challenges of implementing recycling technologies, reviews global practices, and proposes a framework for improving resource efficiency and reducing environmental impact. It highlights the economic benefits, including cost savings and job creation. Methodologically, the research relied on a descriptive analytical approach, supplemented by questionnaires, expert interviews, field observations, and technical document analysis. Drawing on reliable sources, including World Bank and United Nations reports, the study aims to provide practical recommendations for engineers, contractors, and decision-makers to promote sustainable waste management practices in line with the country’s digital and environmental goals.